Discrimination, harassment and non‐reporting in UK medical education. Issue 4 (25th March 2018) - Broad, Jonathan; Matheson, Marion; Verrall, Fabienne; Taylor, Anna K; Zahra, Daniel; Alldridge, Louise; Feder, Gene
Abstract : Context: Discrimination and harassment create a hostile environment with deleterious effects on student well‐being and education. In this study, we aimed to: (i) measure prevalences and types of discrimination and harassment in one UK medical school, and (ii) understand how and why students report them. Methods: The study used a mixed‐methods design. A medical school population survey of 1318 students was carried out in March 2014. Students were asked whether they had experienced, witnessed or reported discrimination or harassment and were given space for free‐text comments. Two focus group sessions were conducted to elicit information on types of harassment and the factors that influenced reporting. Proportions were analysed using the Wilson score method and associations tested using chi‐squared and regression analyses. Qualitative data were subjected to framework analysis. Degrees of convergence between data were analysed. Results: A total of 259 (19.7%) students responded to the survey. Most participants had experienced (63.3%, 95% confidence interval [CI]: 57.3–69.0) or witnessed (56.4%, 95% CI: 50.3–62.3) at least one type of discrimination or harassment. Stereotyping was the form most commonly witnessed (43.2%, 95% CI: 37.4–49.3). In the qualitative data, reports of inappropriate joking and invasion of personal space were common. Black and minority ethnic students had witnessed and religious students had experienced a greater lack of provision (χ 2  = 4.73, p = 0.03 and χ 2  = 4.38, p = 0.04, respectively). Non‐heterosexual students had experienced greater joking (χ 2  = 3.99, p = 0.04). Students with disabilities had experienced more stereotyping (χ 2  = 13.5, p < 0.01). Female students and students in clinical years had 2.6 (95% CI: 1.3–5.3) and 3.6 (95% CI: 1.9–7.0) greater odds, respectively, of experiencing or witnessing any type of discrimination or harassment. Seven of 140 survey respondents had reported incidents (5.0%, 95% CI: 2.4–10.0). Reporting was perceived as ineffective and as potentially victimising of the reporter. Conclusions: Harassment and discrimination are prevalent in this sample and associated with gender, ethnicity, sexuality, disability and year group. Reporting is rare and perceived as ineffective. These findings have informed local developments, future strategies and the development of a national prevention policy. Abstract : Broad and colleagues study the prevalence of various types of harassment and discrimination and provide data to help understand reporting behaviours